Acute Illness Protocol for Organic Acidemias: Methylmalonic Acidemia and Propionic Acidemia. Issue 2 (February 2017) - Aldubayan, Saud H.; Rodan, Lance H.; Berry, Gerard T.; Levy, Harvey L.
Abstract : Abstract: Inborn errors of metabolism (IEM) are genetic disorders that disrupt enzyme activity, cellular transport, or energy production. They are individually rare, but collectively have an incidence of 1:1000. Most patients with IEMs are followed by a physician with expertise in Biochemical Genetics (Metabolism), but may present outside of this setting. Because IEMs can present acutely with life-threatening crises that require specific interventions, it is critical for the emergency medicine physicians, pediatricians, internists, and critical care physicians as well as biochemical geneticists to be familiar with the initial assessment and management of patients with these disorders. Appropriate early care can be lifesaving. This protocol is not designed to replace the expert consultation of a biochemical geneticist but rather to improve early care and increase the level of comfort of the acute care physician with initial management of organic acidemias until specialty consultation is obtained.